Relationship between duration of physical exercise and menstrual cycle female athletes in East Java Sports High School - Paula Eka Romadona (Indonesian Journal of Social Sciences, 2021)
Exercise can be a supporting factor or inhibitor of reproductive health related to menstruation. East Java Sports High School is a particular school for athletes who have more intensive physical training than other public schools. This research was conducted to determine whether there is a significant relationship between the duration of physical exercise and the menstrual cycle in female athletes at East Java Sports High School. The method of this research is quantitative, with a sample of 60 respondents from 14 sports. Data is processed and calculated with Microsoft Excel and SPSS version 21, the statistical test used chi-square test. The calculation results obtained were 0.002 <0.05, so there is a significant relationship between the duration of physical exercise and the athlete's menstrual cycle at East Java Sports High School. That can be caused by excessive use of energy when practicing so that the energy in the body is out of balance which results in decreased pulsatile GnRH, which can affect FSH. In addition, the results of calculations on the variable menstrual disorders in the form of physical disorders during menstruation obtained results 0.565 >0.05, so there is no significant relationship between the duration of physical exercise with menstrual disorders in athletes at East Java Sports High School.